(untitled) (PERcursos Linguísticos, 2021)
In Portuguese language classes, the emphasis on nomenclatures and classifications, based on Traditional Grammar, is still common. However, when working with reading, interpreting and textual production activities, we realize that grammatical knowledge alone is not sufficient for the development of communicative competence in students. Thus, in this article, we will present our understanding of mother tongue teaching, based on studies carried out by important Brazilian linguists. Subsequently, we will present a proposal for activities that was applied to high school students, followed by a brief analysis of the elements present in it. The activity is based on Luís Fernando Veríssimo chronicle entitled “Demands of Modern Life” and was proposed for the face-to-face modality, prior to the pandemic. We take as a basis authors such as Sírio Possenti, Irandé Antunes, Ferrarezzi and Carvalho and Juanito Avelar, who are important references with regard to the issue of Portuguese language teaching in Brazil.